Six Sigma Technique to Reduce Waiting Time: A Practical Application in Passport Affairs Directorate - Khudair Abbas, Hadeel; Mohammed Nasser, Omar (Journal of Economics and Administrative Sciences, 2024)
This study investigates the impact of the Six Sigma methodology on improving waiting times in passport directorates. The Six Sigma methodology is crucial for enhancing efficiency and effectiveness in passport directorates, aiming to reduce waiting times and increase customer satisfaction by organizing services more effectively. The research was conducted in the Passport Affairs Department (Mansour Passports) from November 8, 2022, to April 19, 2023, with a sample size of 53 employees and citizens. The problem of this study is to shed light on the role played by the Six Sigma methodology in improving waiting time at the Passport Affairs Department. The study adopted the DMAIC methodology (Define, Measure, Analyze, Improve, and Control) and used statistical software (SPSS) to calculate Six Sigma levels for both citizens and employees. Access and service data analysis was conducted using Win QSB software, and arrival and service times were calculated for all stages (counter employees, accounts, and manager's computer). The most significant results indicate that the directorate operates at the first level of Sigma levels, while citizens are at the second level. There is a significant and inverse effect of Six Sigma principles on waiting. The total time a citizen waits from entering the passport office to receiving their passport is very long. Paper type: Research Paper